EFEKTIVITAS TEPUNG BUAH MAHKOTA DEWA (Phaleria macrocarpa) UNTUK PENGOBATAN INFEKSI BAKTERI AEROMONAS HYDROPHILA PADA IKAN LELE SANGKURIANG - Sri Muntari; Ade Dwi Sasanti; Ferdinand Hukama Taqwa (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT The aim of this research was to examine Phaleria macrocarpa fruit powder mixed on feed in order to cure infected sangkuriang catfish by A. hydrophila. The advantage of this research was as an alternatives method using Phaleria macrocarpa fruit powder to cure sangkuriang catfish infected by A. hydrophila. This research was conducted on Laboratorium Budidaya Perairan, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University. Determination of hematocrit and total leucocytes were conducted in UPT Klinik Sriwijaya University, Indralaya from October until November 2014. This research was  designed based on Complete Randomized Design with six treatments and three replications. The fish was infected by A. hydrophila with density of 2.2.106 cfu.mL-1 using injection method. The catfish has been reared for 31 days and fed with pellet enriched  with 0 %, 1.2 %, 2.4 %, 3.6 % and 4.8 % Phaleria macrocarpa fruit powder. Feeding frequency was three times a day. The parameters observed on this research were injury diameter, the percentage of cured fish, hematocrit concentration, total leucocytes, survival rate, growth, feed efficiency and water physical and chemical properties. The result showed that the addition of P. macrocarpa fruit powder on feed was effectively cured the infection caused A. hydrophila revealed by decreasing of injury diameter. The best treatment was the addition of 2.4 % P. macrocarpa. This treatment could increase hematocrit concentration and total leucocytes, gave the highest results on survival rate (95 %), absolute weight growth (22.4 g), absolute length growth (5.38 cm) and feed efficiency (77.9 %).     Keywords : Aeromonas hydrophila, catfish, infection, treatment, P. macrocarpa